Bone relapse in T-lineage acute lymphoblastic leukemia in a child. Issue 10 (24th September 2018) - Meena, Jagdish Prasad; Ahad, Abdul; Gupta, Aditya Kumar; Mallick, Saumyaranjan; Seth, Rachna
Abstract: Acute lymphoblastic leukemia (ALL) is the most common malignancy in children. T-cell ALL accounts for 10–15% of cases. ALL can rarely relapse in unusual extramedullary sites like bone. Hereby, we report a case of 7-year-old male child who was being treated for T-cell ALL and then presented with left arm swelling. This swelling was initially thought to be a bone tumor but later it was found to be infiltrated by leukemic blasts. We reviewed all previous cases and suggest that in a patient of ALL presenting with a bone swelling during or after completion of therapy, one should suspect of bone relapse.